The Astigmatism Profile Overview of Visitors to Optik X - Prihanto, Muhammad Ilham; Lesmana, Michael Indra; Hudyono, Johannes (Jurnal MedScientiae, 2025)
Astigmatism is a common refractive error that can affect visual quality. Understanding the profile of astigmatism is essential to provide accurate vision correction. Purpose : describe the astigmatism profile based on age, gender, type of astigmatism, and meridian axis among visitors of Optik Melawai Living World Alam Sutera in 2025. Methods: This is a descriptive quantitative study using a cross-sectional design. The study involved 146 randomly selected participants who met the inclusion criteria. Data were collected through subjective refraction examinations using a phoropter and Snellen chart. Results : Astigmatism was most commonly found in females (54.8%) and in the 22-27 years age group (30.8%). The most common type of astigmatism was Compound Myopic Astigmatism, found in 71.2% of both right and left eyes. The dominant meridian axis was With the Rule in 51.3% of cases in both eyes. Conclusion: Compound Myopic Astigmatism and With the Rule meridian axis are the most common astigmatism profiles found among visitors at Optik Melawai Living World Alam Sutera in 2025. Careful refraction examinations and good communication between examiner and patient are essential to ensure accurate measurement results.